If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(h+3)=-18
We move all terms to the left:
9(h+3)-(-18)=0
We add all the numbers together, and all the variables
9(h+3)+18=0
We multiply parentheses
9h+27+18=0
We add all the numbers together, and all the variables
9h+45=0
We move all terms containing h to the left, all other terms to the right
9h=-45
h=-45/9
h=-5
| –7(–5n+9)=11(n+3)–8n | | -1x-10+2x=-1 | | 75=27x-3x+1+2 | | 7k-11=3k-3 | | 65-x=65 | | 10(4/5x-x)=10(x/10-15/2) | | 2x–7=2x+4 | | y=4+7×2 | | 11x+5+17x-19=180 | | -80=x-60 | | -10(x+3)=20(-1/2x+1)-2+12 | | 27=66x+6x+1+2 | | 5-(2x+3)=4x-10 | | 12.50+3/9=x | | 2x+(6x-7)=(103-x) | | 33=99-x | | 2(1/2x-6)=11 | | (x)=3x^2+1 | | 100=12x+13Y | | F(-5)=x^2-2x+7 | | (9x+16)(19x+3)(6x+15)=180 | | 3r=-42 | | 12.50+5/9=x | | 12=15n=33 | | 1x+1.2x-5.4=−10 | | 2({1}{2}x-6)=11 | | -28=x+4 | | 3(x-5)^2=363 | | 2/3x-8=x-17 | | 27=12x+6x+1+2 | | (2x+3)=(9x-25) | | 12(f+5)=138 |